FAKTOR-FAKTOR YANG MEMENGARUHI ANGKA KEBUNTINGAN (CONCEPTION RATE) PADA SAPI POTONG SETELAH DILAKUKAN SINKRONISASI ESTRUS DI KABUPATEN LAMPUNG TENGAH - Zulfi Al Arif; Madi Hartono; Sri Suharyati (JURNAL ILMIAH PETERNAKAN TERPADU, 2014)
This research used 287 cattle cows owned by 198 breeders, involve 3 sub-districts in Central Lampung District.This research aimed to determine factors affecting conception rate after oestrous synchronization in cattle cows inCentral Lampung District, Lampung Province in November 2012-Februari 2013.The result of this research showed that the conception rate cattle cows after oestrous synchronization in CentralLampung District was 60,53 %, included in less good category. The factors affecting conception rate after oestroussynchronization in Central Lampung District were the amount of pasture given which positively associate with thefactor amount of 0,020, the shape of cage wall which negatively associate with the factor amount of 1,473, thematerial of cage floor which positively associate with the factor amount of 0,701, the cage width which negativelyassociate with the factor amount of 0,062, & the breeding long time which positively associate with the factoramount of 0,057.